Killing two birds with a single stone—genetic manipulation of cytokinin oxidase/dehydrogenase (CKX) genes for enhancing crop productivity and amelioration of drought stress response - Sharma, Aman; Prakash, Subasty; Chattopadhyay, Debasis (Frontiers in Genetics, 2022)
The development of high-yielding, bio-fortified, stress-tolerant crop cultivars is the need of the hour in the wake of increasing global food insecurity, abrupt climate change, and continuous shrinking of resources and landmass suitable for agriculture. The cytokinin group of phytohormones positively regulate seed yield by simultaneous regulation of source capacity (leaf senescence) and sink strength (grain number and size). Cytokinins also regulate root-shoot architecture by promoting shoot growth and inhibiting root growth. Cytokinin oxidase/dehydrogenase (CKX) are the only enzymes that catalyze the irreversible degradation of active cytokinins and thus negatively regulate the endogenous cytokinin levels. Genetic manipulation of CKX genes is the key to improve seed yield and root-shoot architecture through direct manipulation of endogenous cytokinin levels. Down-regulation of CKX genes expressed in sink tissues such as inflorescence meristem and developing seeds, through reverse genetics approaches such as RNAi and CRISPR/Cas9 resulted in increased yield marked by increased number and size of grains. On the other hand, root-specific expression of CKX genes resulted in decreased endogenous cytokinin levels in roots which in turn resulted in increased root growth indicated by increased root branching, root biomass, and root-shoot biomass ratio. Enhanced root growth provided enhanced tolerance to drought stress and improved micronutrient uptake efficiency. In this review, we have emphasized the role of CKX as a genetic factor determining yield, micronutrient uptake efficiency, and response to drought stress. We have summarised the efforts made to increase crop productivity and drought stress tolerance in different crop species through genetic manipulation of CKX family genes.